Hydro biological indicators of reservoirs of the Akmola and Karaganda regions for 2017 - Mamytova, N.S.; Akbaeva, L.Kh.; Malashenkov, D.V.; Tulegenov, E.A. (Pub KSU, 2019)
On the territory of Akmola and Karaganda regions, hydro biological indicators were studied in the lakes Korgalzhinskoe, Esey, Kokai; in the reservoirs of Samarkand and Kengir; in the rivers Nura, Sherubainura, Kara Kengir. In 2017, selected phytoplankton species, zooplankton, periphyton, and benthos were studied in selected surface waters that are experiencing increasing anthropogenic pressure. A list of phytoplankton species, zooplankton, periphyton, and benthos has been compiled, the characteristic features of their distribution are noted. The dominant phyto, zooplankton and periphyton species were also identified. Also indexes of Sladechek's saprobity were calculated and compared, and a general ecological assessment of reservoirs and watercourses was given. It was revealed that the studied surface waters of the Akmola and Karaganda regions belong to the 3rd class of water quality, mesotrophic, β-mesasaprobic in terms of the quality of water. For water bodies of the beta-mezasaprobic zone of the Akmola and Karaganda regions, coenotic communities of aquatic organisms differ in varying species composition, which does not depend on the same landscape and climatic conditions. The periphyton and benthic community in rivers has a tendency to higher rates of saprobity compared to other hydrobiont communities: the periphytonsaprobity indices and the Woodwiss index are higher than the phytoplankton saprobity indices
2017 жылғы Ақмола жəне Қарағанды облыстарының су нысандарының гидробиологиялық көрсеткіштері
Гидробиологические показатели водоемов Акмолинской и Карагандинской областей за 2017 год
Keywords: saprobity; hydrobionts; test objects; indicators; zooplankton; phytoplankton; periphyton; zoobenthos